Tangible user interface design for learners with different multiple intelligence - Salintip Sudsanguan; Sakchai Tangwannawit; Thippaya Chintakovid (International Journal of Electrical and Computer Engineering (IJECE), 2021)
The creation of learning activities responsive to learners with different basic skills has been limited due to a classroom environment and applied technologies. The goals of this research were to develop Tang-MI, a game with a tangible user interface supporting primary school learners’ analytical skills based on the theory of multiple intelligences (MI), and to present design guidelines for a tangible user interface suitable for learners in different MI groups. In this research, the Tangible user interface for multiple intelligence (Tang-MI) was tested with thirty students initially evaluated for their multiple intelligences. The learners’ usage behavior was observed and recorded while the students performed the assigned tasks. The behavioral data were analyzed and grouped into behaviors occurring before performing the tasks, during the tasks, and after completing the tasks. Based on the learners’ usage behavior, the tangible user interface design guidelines for learners in different MI groups were proposed concerning physical equipment design, question design, interactive program design, audio design, and animated visual feedback design. These guidelines would help educators build learning games that respond to the learners’ intelligence styles and enhance students’ motivation to learn.